Three-dimensional analysis of heat transfer in a channel provided with solid baffle, single and double perforation A heat exchanger application - Benzenine, Hamidou; Saim, Rachid; Abboudi, Said; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Emerald Group Publishing Ltd, 2020)
Purpose The purpose of this paper is to present a three-dimensional (3D) analysis of the laminar flow of air and the conjugate heat transfer in a pipe of rectangular cross-section with a solid or perforated deflector inserted on the lower wall. Design/methodology/approach To this end, by using the finite volume method, the conservation equations for mass, momentum and energy are solved numerically. Two cases of single and double perforation were studied and compared with that of the solid case for a range of Reynolds numbers ranging from 140 to 840. The velocity and temperature profiles were plotted and interpreted on three different sections placed sequentially upstream, mid-stream and downstream of the deflector. Total heat exchange at the bottom wall, outlet fluid temperature, perforated PFE deflector performance and pressure loss is presented for different cases studied and for different Reynolds numbers. Findings The results show that although the perforated deflector improves the heat transfer, it also results in additional pressure losses; the study also showed the existence of a limiting velocity beyond which the perforation effect on the improvement of the heat exchange decreases until the same performance of the solid deflector is achieved. Originality/value The main originality of this work is to show a 3D analysis for a perforated baffle as heat exchanger application.
Keywords: Finite volume method; Laminar flow; Perforated baffle; Solid baffle; Three-dimensional forced convection